Intra- and interspecific mineral composition variability of commercial instant coffees and coffee substitutes: contribution to mineral intake - Oliveira, Marta (2013)
The present paper reports the amount and estimated daily mineral intake of nine elements (Ca, Mg, K, Na, P, Fe, Mn, Cr and Ni) in commercial instant coffees and coffee substitutes (n = 49). Elements were quantified by high-resolution continuum source flame (HR-CS-FAAS) and graphite furnace (HR-CS-GFAAS) atomic absorption spectrometry, while phosphorous was evaluated by a standard vanadomolybdophosphoric acid colorimetric method. Instant coffees and coffee substitutes are rich in K, Mg and P (>100 mg/100 g dw), contain Na, Ca and Fe in moderate amounts (>1 mg/100 g), and trace levels of Cr and Ni. Among the samples analysed, plain instant coffees are richer in minerals (p < 0.001), except for Na and Cr. Blends of coffee substitutes (barley, malt, chicory and rye) with coffee (20–66%) present intermediate amounts, while lower quantities are found in substitutes without coffee, particularly in barley. From a nutritional point of view the results indicate that the mean ingestion of two instant beverages per day (total of 4 g instant powder), either with or without coffee, cannot be regarded as important sources of minerals to the human diet, although providing a supplementation of some minerals, particularly Mg and Mn in instant coffees. Additionally, and for authentication purposes, the correlations observed between some elements and the coffee percentage in the blends, with particular significance for Mg amounts, provides a potential tool for the estimation of coffee in substitute blends.